2021
DOI: 10.1002/cam4.3808
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and risk of gastric cancer: A population‐based prospective cohort study

Abstract: The recognition of adiposity as a risk factor for gastric cancer is mainly based on traditional anthropometric indices, such as body mass index, which are unable to discriminate between lean and fat mass. We undertook this study to examine body composition and subsequent risk of gastric cancer. This is a prospective analysis of participants free of cancer from the UK Biobank. We measured baseline body composition with electrical bioimpedance analysis and confirmed cancer diagnosis through linkage to cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Changes in anthropometric parameters, including weight, BMI, waist circumference, waist‐to‐hip ratio, FM, and FFM, reflect an individual's nutritional status to some extent and can, therefore, greatly predict the risk and prognosis of chronic diseases, including cancer 17,18 . Similar to our partial results, some studies based on the UK Biobank have also shown that FFM is strongly associated with the risk of all cancers, including lung and digestive system cancers 7,19,20 . Another study on body composition using dual‐emission X‐ray absorptiometry also demonstrated a significant association between FFM and the malignancy of prostate cancer 21 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Changes in anthropometric parameters, including weight, BMI, waist circumference, waist‐to‐hip ratio, FM, and FFM, reflect an individual's nutritional status to some extent and can, therefore, greatly predict the risk and prognosis of chronic diseases, including cancer 17,18 . Similar to our partial results, some studies based on the UK Biobank have also shown that FFM is strongly associated with the risk of all cancers, including lung and digestive system cancers 7,19,20 . Another study on body composition using dual‐emission X‐ray absorptiometry also demonstrated a significant association between FFM and the malignancy of prostate cancer 21 .…”
Section: Discussionsupporting
confidence: 87%
“…17,18 Similar to our partial results, some studies based on the UK Biobank have also shown that FFM is strongly associated with the risk of all cancers, including lung and digestive system cancers. 7,19,20 Another study on body composition using dual-emission X-ray absorptiometry also demonstrated a significant association between FFM and the malignancy of prostate cancer. 21 At the same time, there are also some heterogeneous conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…Body shape not only reflects the weight information, but also reflects the information of body composition ( 23 ). In order to reduce recall bias and incorporate body composition information into the analysis, our study used Stunkard body shape as a component of lifestyle variables ( 9 , 38 ). Consistent with previous studies, our study also found that a suitable body size is associated with a lower GC risk ( 10 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of large-scale cohort studies and meta-analyses have examined the relationship between smoking ( 6 ), alcohol drinking ( 7 ), poor oral hygiene habits ( 8 ), BMI and body composition ( 9 , 10 ), diet ( 11 15 ), physical activity ( 16 18 ) and the risk of GC. The observed reduced GC risk associated with refrigerator usage also suggests that food storage method may be one of the GC-risk-related lifestyle factors ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…www.co-urology.com analyzing weight without taking into consideration the different body compositions can lead to different biases. A recent population-based prospective cohort study by Liu et al [22] reported that both male (HR ¼ 1.70) and female patients (HR ¼ 2.47) with higher levels of body fat-free mass had a higher risk of gastric cancer [22]. In contrast, in female patients fat mass was identified as a protective factor of gastric cancer (HR per 5-unit increase 0.86).…”
Section: Key Pointsmentioning
confidence: 99%